A Tetramethylplatinum(IV) Complex with 1,1 '-Bis(diphenylphosphanyl)ferrocene Ligands: Reaction with Trifluoroacetic Acid - Shahsavari, Hamid R.; Rashidi, Mehdi; Nabavizadeh, S. Masoud; Habibzadeh, Sepideh; Heinemann, Frank Wilhelm (European Journal of Inorganic Chemistry, 2009)
A new tetramethylplatinum(IV) complex [PtMe4(dppf)] [2; dppf = 1,1'-bis(diphenylphosphanyl)ferrocene], as the first platinum(IV) complex to contain a chelating dppf ligand, was prepared by the reaction of the known dimeric tetramethylplatinum(IV) complex cis, cis-[Me4Pt(mu-SMe2)(2)PtMe4] (1) with the biphosphane ligand dppf (2 equiv.) at room temperature by replacement of the SMe2 ligands with the P ligating atoms of dppf. The single-crystal X-ray structure of complex 2 revealed that the dppf chelating ligand is arranged close to the "synperiplanar-eclipsed" conformation, with a Cp(centroid)center dot center dot center dot Fe center dot center dot center dot Cp(centroid) twist angle of 17.6 degrees and a dppf bite angle, P1-Pt1-P2, of 95.77(3)degrees. This is in contrast to the usually pref erred "synclinal-staggered" conformation, in which the Cp(centroid)center dot center dot center dot Fe center dot center dot center dot Cp(centroid) twist angle is close to 36 degrees as found in Pt-II complexes with chelating dppf ligands, like for example [PtMe2(dppf)] exhibiting a dppf bite angle close to 100 degrees. When complex 2 was treated with the strong acid CF3COOH (1 equiv.) first evolution of methane was observed, followed by a C-C coupling reaction to give ethane and the methylplatinum(II) complex [PtMe(OCOCF3)(dppf)] (3). The reaction of complex 2 with the nucleophile HgCl2 (1 equiv.) similarly gave MeHgCl, ethane, and the methylplatinum(II) complex [PtMeCl(dppf)] (11). The structure of complex 3 was also determined by X-ray crystallography. The geometry around the platinum center is best described as distorted square-planar and the dppf is arranged in the usually preferred "synclinal-staggered" conformation. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)
Keywords: Platinum; Metallocenes; P ligands; Conformation analysis